Mapping Serbia's Growth - World Bank (Washington, DC, 2013)
Big cities are becoming even bigger and these have been and will be the key drivers of economic growth in Serbia. Belgrade, Novi Sad, Nis and Kragujevac, Serbia's four largest cities contributed to about 60 percent of the increase of value added in the economy over the period 2001-2008. These four largest cities in 2008 accounted for about two thirds of country s economy. Spatial characteristics of foreign direct investments inflow, privatization process and location of export oriented sectors, indicate significant concentration. FDI and privatization were attracted by largest cities, though the proximity to the key transit routes, like Corridor 10, is also important for making decision where to invest. Export is concentrated in several places, depending on the type of production, and proximity of major export markets contributed to concentration of export near the borders of the EU (i.e., Hungary) and Bosnia and Herzegovina, the second most important export market for Serbia. Spatially uneven growth caused differences in living standards. Wages did not play significant role, as migrations did in adjusting differences in economic development among regions. Living standards are lowest in southern Serbia which has on average negative growth rates over this period and where both unemployment and poverty are highest. The last section of the report discusses some of the possible options for policy makers as response to spatially biased growth.